Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1021/ja301264v
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Partitioning of Nano/Microparticles Mediated by Membrane Lateral Heterogeneity

Abstract: It is important that we understand the physical, chemical, and biological mechanisms that govern the interaction between nanoparticles (NPs) and heterogeneous cellular surfaces because of the possible cytotoxicity of engineered nanomaterials. In this study, we investigated the lateral localization of nano/microparticles within a biomimetic heterogeneous membrane interface using cell-sized two-phase liposomes. We found that lateral heterogeneity in the membrane mediates the partitioning of nano/microparticles i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
60
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 62 publications
(92 reference statements)
1
60
1
Order By: Relevance
“…19,20 Consequently, nanoparticles have been observed to adsorb onto the outer leaflet of membranes, incorporate within a membrane, or cause the deformation of membranes to generate nanoscale holes. 2124 In the case of hydrophobic 2.0–5.0 nm QDs, electron and optical microscopy indicate that the nanoparticles partition into the hydrophobic region of the lipid membranes. 17 Given that the typical diameter of QDs is commiserate with the typical thickness of phospholipid membranes, it is not clear how the QD distorts the organization of the lipid bilayer, and correspondingly, how the organization of the lipid membrane influences the physical and chemical properties of the semiconductor nanocrystal.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Consequently, nanoparticles have been observed to adsorb onto the outer leaflet of membranes, incorporate within a membrane, or cause the deformation of membranes to generate nanoscale holes. 2124 In the case of hydrophobic 2.0–5.0 nm QDs, electron and optical microscopy indicate that the nanoparticles partition into the hydrophobic region of the lipid membranes. 17 Given that the typical diameter of QDs is commiserate with the typical thickness of phospholipid membranes, it is not clear how the QD distorts the organization of the lipid bilayer, and correspondingly, how the organization of the lipid membrane influences the physical and chemical properties of the semiconductor nanocrystal.…”
Section: Introductionmentioning
confidence: 99%
“…Since there is no asymmetry in the vesicle encapsulating the reconstituted cytoskeleton, the directional motion can not be realized. Recently, we reported asymmetric adhesion of colloids to the membrane due to the phase separation on the membrane as described below [47]. Using this technique, the asymmetry can be induced in the reconstituted cytoskeleton.…”
Section: Complex System Of Membranes and Nanoparticlesmentioning
confidence: 97%
“…Several studies on membrane–colloid interactions with homogeneous cell-sized liposomes have reported that polystyrene particles spontaneously adhere to a phosphatidylcholine (PC) membrane surface [31,32]. We investigated the association of polystyrene NPs within biomimetic membrane interfaces with lateral heterogeneity, such as two-phase liposomes [33]. Two-liquid Lo/Ld separated liposomes were composed of saturated and unsaturated PC lipids (dipalmitoyl phosphatidylcholine, DPPC, and dioleoyl phosphatidylcholine, DOPC) together with cholesterol (Chol) (DOPC/DPPC/Chol = 37:37:26, molar ratio).…”
Section: Association On Soft Membranesmentioning
confidence: 99%
“…Scale bars are 10 µm; ( b ) Schematics of the size-dependent selective localization of NPs. Reprinted with permission from [33]. Copyright 2010 American Chemical Society.…”
Section: Association On Soft Membranesmentioning
confidence: 99%